2,3,4,6-Tetra-O-(3-nitropropanoyl)-O-β-D-glucopyranoside, a new antimicrobial from the roots of Heteropteris aphrodisiaca - Roman Jr., Walter Antônio [UNESP]; Cardoso, Mara Lane Carvalho; Vilegas, Wagner [UNESP]; Nakamura, Celso Vataru; Dias Filho, Benedito Prado; De Mello, João Carlos Palazzo [UNESP] (My University, 2005)
A new 2,3,4,6-tetra-O-(3-nitropropanoyl)-O-β-D-glucopyranoside anomer was isolated from the roots of Heteropteris aphrodisiaca and characterized by spectroscopic methods. Activity against Staphylococcus aureus, Bacillus subtilis, Candida albicans, C. parapsilosis, C. krusei, and C. tropicalis was demonstrated.
Keywords: 2,3,4,6-tetra-O-(3- nitropropanoyl)-O-β-D-glucopyranoside; Heteropteris aphrodisiaca; Malpighiaceae; Nitrocompound; 2,3,4,6 tetra o (3 nitropropanoyl) o beta dextro glucopyranoside; antiinfective agent; nitro derivative; plant extract; unclassified drug; antibacterial activity; antimicrobial activity; Bacillus subtilis; Candida albicans; Candida krusei; Candida parapsilosis; Candida tropicalis; controlled study; drug isolation; fungicidal activity; infrared spectroscopy; mass spectrometry; minimum inhibitory concentration; nonhuman; nuclear magnetic resonance spectroscopy; plant root; Staphylococcus aureus